2018
DOI: 10.1017/s0007114518000405
|View full text |Cite
|
Sign up to set email alerts
|

Dietary inflammatory index and risk of oesophageal cancer in Xinjiang Uyghur Autonomous Region, China

Abstract: Diet has been shown to have an effect on both inflammation and oesophageal cancer. This study investigated the association between the dietary inflammatory index (DII®) and the risk of oesophageal cancer in Xinjiang Uyghur Autonomous Region, China. A case-control study was conducted during 2008-2009 in Urumqi and Shihezi. DII scores were calculated based on dietary intake assessed by a validated FFQ administered to 359 incident oesophageal cancer patients and 380 hospital-based controls. Higher DII scores indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 56 publications
1
19
0
Order By: Relevance
“…Of the 53 studies retrieved for full-text review, 24 met the selection criteria ( Figure 1 and Table 1 ). UGI cancers were identified by self-reported questionnaire [ 7 , 8 , 10 ], physician-reviewed pathology records [ 7 , 8 , 10 ], linkage to cancer registry system [ 5 , 6 , 7 , 8 , 10 , 11 ], or pathological confirmation [ 9 , 12 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. All included cohort studies were rated as high-quality (7–9 points) ( Supplementary Material 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 53 studies retrieved for full-text review, 24 met the selection criteria ( Figure 1 and Table 1 ). UGI cancers were identified by self-reported questionnaire [ 7 , 8 , 10 ], physician-reviewed pathology records [ 7 , 8 , 10 ], linkage to cancer registry system [ 5 , 6 , 7 , 8 , 10 , 11 ], or pathological confirmation [ 9 , 12 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. All included cohort studies were rated as high-quality (7–9 points) ( Supplementary Material 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…We included two cohort studies [ 5 , 8 ] and seven case-control studies [ 9 , 27 , 28 , 29 , 30 , 31 , 36 ] that used the DII. The quantitative analysis included 519,741 subjects from cohort studies (mean follow-up, 14.5 years) and 5776 subjects from case-control studies.…”
Section: Resultsmentioning
confidence: 99%
“…Analyses conducted in the Asklepios study of 2524 generally healthy adult Belgian adults showed significant positive associations between DII scores and the inflammatory markers IL-6 (>1.6 pg/ml) (OR=1.19, 95%CI:1.04-1.36) and homocysteine (>15 μmol/l) (OR=1.56, 95%CI:1.25-1.94) (22). A higher (more pro-inflammatory) DII score has been associated with increased risk of asthma (20), cardiovascular disease (23), and cancers of the colorectum (24-33), pancreas (34, 35), esophagus (36-39).…”
Section: Introductionmentioning
confidence: 99%
“…This study observed that 24% increased risk of developing ESCC for each unit higher of the DII scores (pooled RR: 1.24; 95% CI: 1.10–1.38) [7]. Similar results were found in Japan [8], China [9], Iran [10], Italy [11], and Sweden [12].…”
Section: Introductionmentioning
confidence: 52%